Free Amino Acids in Different Organs of Scutellaria baicalensis - Bok Kim, Yeon; Romij Uddin, Md; Lee, Min-Ki; Kim, Sun-Ju; Hoon Kim, Haeng; Lee, Jai-Heon; Un Park, Sang (Asian Journal of Chemistry, 2014)
We investigated the free amino acids content in different plant parts of golden root (Scutellaria baicalensis) and identified 21 different free amino acids, the levels of which varied widely between organs. The amount of free amino acids in the flower was much higher than that in the leaf (3.4-fold), stem (1.9-fold) and root (5.3-fold). Most of the free amino acids were present in higher amounts in the flower; in particular, a markedly higher amount of glutamine was observed in the flower, which contained 27, 11 and 2 times more glutamine than the root, leaf and stem. Norvaline was found only in the root, which also contained much higher amounts of leucine (37-, 28- and 9-fold higher than in the leaf, stem and flower). Our findings demonstrate that S. baicalensis contains varying amounts of free amino acids between plant tissues and the levels were the highest in the flower.